Peran Kebijakan Fiskal dalam Mengatasi Kemiskinan di Indonesia: Tinjauan Ekonomi Syariah - Rukiah Lubis; Ulan Dari Daulay (Tazkir: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2022)
Poverty alleviation efforts are continuously being carried out by every country in the world, especially Indonesia. Various programs and policies have been implemented by the government as an intermediary in overcoming this problem with various fiscal policy issues in the form of fuel increases, taxes, external debt and APBN budget predictions where these policies are considered bad for the community because they are not targeted and is uneven. The purpose of this study is to analyze the role of tax policy in alleviating poverty in Indonesia based on an economic review of Sharia. This study uses a Content Analysis through a qualitative approach. The conclusion of this study is that the measures implemented by the government to alleviate poverty have not been optimal. Islam finds the solution to less poverty through the zakat instrument. Islamic teachings lay the fundamental foundation for people's socio-economic growth and development through the concept of zakat, hence it is not wrong that the government considers zakat policy as one of the efforts to alleviate the poverty problem in Indonesia. As for the zakat policy in this matter, one of them is productive zakat in the form of capital and education for Small and Medium Enterprises and  optimizing the role of Amil Zakat Institution for the benefit of the Ummah.